Implementation of Health Center Management Policies on the Quality of Health Services - Farhani, Nadya; Adhani, Rosihan; Ringoringo, Harapan Parlindungan; Istiqomah, Ermina; Hartoyo, Edi; Nugorho, Adi (Lambung Mangkurat University, 2025)
Effective management is essential for health centers to ensure that health service standards are met through proper planning, implementation, supervision, and evaluation. One method to assess service quality at Community Health Centers is the Health Center Performance Assessment, which evaluates activity coverage, service quality, and management. Given the crucial role of management in improving health service quality, the implementation of health center management practices is critical. This study explores the obstacles to effective health center management in Tabalong District. A qualitative approach was employed using a case study design. Data were collected through in-depth interviews, focus group discussions (FGDs), observations, and documentation involving 15 informants from the District Health Office and several health centers. Despite efforts to adhere to Minister of Health Regulations No. 6/2016 and No. 19/2020, several challenges persist, including non-functional SMD–MMD activities and mini-workshops that do not follow established guidelines. Additional barriers include limited human resources, budget constraints, incomplete standard operating procedures (SOPs), and fragmented information systems. In conclusion, the implementation of health center management has not been fully optimal, resulting in service quality that has yet to meet expected standards.